2019
DOI: 10.1038/s41393-019-0361-6
|View full text |Cite
|
Sign up to set email alerts
|

All-cause and cause-specific mortality following non-traumatic spinal cord injury: evidence from a population-based cohort study in Switzerland

Abstract: Study design Observational cohort study. Objective To benchmark all-cause and cause-specific mortality following NTSCI to the general population (GP). Setting Specialized rehabilitation centers in Switzerland. Methods Longitudinal data from the Swiss Spinal Cord Injury (SwiSCI) Medical Record study were probabilistically linked with cause of death (CoD) information from the Swiss National Cohort. Standardized mortality ratios (SMRs) were estimated for all-cause and cause-specific mortality. Competing risk fram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 32 publications
0
19
0
1
Order By: Relevance
“…In persons with SCI, the prevalence of heart disease is 17.1 % (ages 65-69 years) compared with 4.9 % (ages 65-69 years) for individuals without SCI, while the odds of heart disease or stroke are more than two and three-folds greater in individuals with SCI in comparison to individuals without SCI, respectively. [7,8] Cardiovascular complications are, therefore, among the leading causes of death in persons with SCI and an important determinant of longevity and quality of life in this vulnerable population [9][10][11]. Thus, there is an emerging need to improve research in this area.…”
Section: Cardiometabolic Risk Following the Spinal Cord Injurymentioning
confidence: 99%
“…In persons with SCI, the prevalence of heart disease is 17.1 % (ages 65-69 years) compared with 4.9 % (ages 65-69 years) for individuals without SCI, while the odds of heart disease or stroke are more than two and three-folds greater in individuals with SCI in comparison to individuals without SCI, respectively. [7,8] Cardiovascular complications are, therefore, among the leading causes of death in persons with SCI and an important determinant of longevity and quality of life in this vulnerable population [9][10][11]. Thus, there is an emerging need to improve research in this area.…”
Section: Cardiometabolic Risk Following the Spinal Cord Injurymentioning
confidence: 99%
“…The index was computed as the sum of the 15-health problems ( , weighted by their estimated mortality risk ( Buzzell et al, 2020 ; Cao et al, 2019 ; DiPiro et al, 2019 ; Frankel et al, 1998 ; Garshick et al, 2005 ; Lidal et al, 2007 ; Minaire et al, 1983 ; Neumann et al, 2009 ; Osterthun et al, 2014 ; Sabre et al, 2013 ; Savic et al, 2017 ; Soden et al, 2000 ; World Health Organization, 2016 ), times the reported severity (see appendix). The severity was ranked as “chronic” (value 2), mild or moderate (value 1), and no problem (value 0).…”
Section: Methodsmentioning
confidence: 99%
“…We use data from the International Spinal Cord Injury Survey [InSCI], which provides for the first-time comparable data on the living situation of persons with SCI from all six WHO regions ( Fekete et al, 2017 ). Due to the lack of mortality data, we use two alternative health measures: (a) the number of years a person has lived with the injury and (b) a co-morbidity index ( Buzzell et al, 2020 ; DiPiro et al, 2019 ; Krause et al, 2011 ; Quan et al, 2011 ). To allow the comparison between countries, a relative personal income was estimated according to the socio-economic position in the country of residence of each respondent.…”
Section: Introductionmentioning
confidence: 99%
“…This DAG therefore also hypothesizes that SCI etiology indirectly impacts mortality through SCI severity. This should be interpreted to mean that the NTSCI etiology, itself causes the SCI severity, which in turn has an impact on survival [ 5 , 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…The reasoning for inclusion of these demographic factors as confounders is based on previous research in the field of SCI [ 7 , 20 ]. ‘Calendar period’ defines a further potential confounding pathway, given that health survey and survival data from the Swiss general population indicate that the survival has steadily increased with calendar period, in addition to the declining risk of death following NTSCI [ 3 , 19 , 21 ].…”
Section: Methodsmentioning
confidence: 99%